Stereospermum fimbriatum as a potential source of phytochemicals: a review of stereospermum genus - Awang, Anis Fadhlina Izyani; Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Sheikh, Hassan Ibrahim; Ghafoor, Kashif; Yunus, Kamaruzzaman (Bentham Science Publishers, 2016)
Stereospermum fimbriatum is one of the medicinal plants that has been claimed to be used traditionally to treat several illnesses such as stomachache, ear-ache, skin irritation and postpartum illness. The genus of this plant is known to pos-sess medicinal properties in every part of the plant. Therapeutic potential of S. fim-briatum is anticipated based on numerous previous studies that documented variety of phytochemical contents and bioactivity of the genus. The most reported bioactiv-ities of its genus are antimicrobial, antioxidant, anti-diabetic, anti-inflammatory, anti-diarrheal and analgesic activities. S. fimbriatum is a rare species that has not been discovered yet. Thus, this review aims at highlighting the potentials of S. fim-briatum by collecting available data on the bioactivities of its genus and set the di-rections for future research on this plant.